Molecular properties of a triazole–Ce(III) complex with antioxidant activity: structure, spectroscopy, and relationships with related derivatives. Influence of the ligands in the complex - Palafox, M. Alcolea; Belskaya, Nataliya P.; Todorov, Lozan; Hristova-Avakumova, Nadya; Kostova, Irena P. (Frontiers in Chemistry, 2024)
A novel Ce(III) complex with the triazole ligand 2b, which presents four H-bonded sites with amino acids of the MMP-2 receptor was synthetized. The experimental IR and Raman spectra of this Ce(III) complex was well interpreted based on their comparison to the theoretical scaled ones using the scaling equations determined by two procedures and four DFT levels. Therefore, the structure predicted for the synthesized Ce(III) complex was clearly characterized and confirmed. The potential antioxidant action of this complex was compared with the analogous La(III) complex, and it was found that coordination of ligand 2b with Ce(III) improves the ligand's ability to participate in Single Electron Transfer (SET), as observed in the ABTS •+ assay, and this complex seems to scavenge the stable radical much more actively, compared to its La(III) counterpart. Additionally, interactions with potassium superoxide and sodium hypochlorite indicate a high pro-oxidant behavior of the complex.The effect of different ligands on the geometric parameters, atomic charges and molecular properties of the Ce(III) complex was analyzed at four DFT levels and several relationships were clearly established. These relationships can facilitate the selection of new ligands with improved properties in the design of novel lanthanide-triazole carboxylate complexes with promising biological activity. The ligand size increase in the complexes facilitates the electronic transfer of negative charge, and the low HOMO-LUMO energy gap indicates a large reactivity and low energy for excitation of them.